Evolution of international environmental regimes : the case of climate change - Schiele, Simone; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
Drawing specifically on the international climate regime, Simone Schiele examines international environmental regimes from a legal perspective and analyses a core feature of international regimes - their ability to evolve over time. In particular, she develops a theoretical framework based on general international law which allows for a thorough examination of the understanding of international law and the options for law-creation in international environmental regimes. The analysis therefore provides both a coherent understanding of the international climate regime and a starting point for further research in other regimes.
Introductory observations and approach -- International environmental regimes and their treaties -- International climate regime -- Effectiveness of international environmental regimes and 'creative legal engineering' -- International regimes as normative systems -- Methodology for determining the norms, sources and underlying theories of international law in the international climate regime -- Sources of legal norms in the international climate regime and the negotiations leading up to and at the Copenhagen conference -- Sources of legal norms in the international climate regime and Compliance Committee methods of interpretation -- Increasing robustness of the international climate regime as a system of norms -- Conclusions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Environmental policy -- International cooperation; Environmental protection -- International cooperation; Environmental law, International; Electronic books